Scopoletin Suppresses Activation of Dendritic Cells and Pathogenesis of Experimental Autoimmune Encephalomyelitis by Inhibiting NF-κB Signaling - Zhang, Fei; Zhang, Yuan; Yang, Ting; Ye, Ze-Qing; Tian, Jing; Fang, Hai-Rong; Han, Juan-Juan; Wang, Zhe-Zhi; Li, Xing (Frontiers in Pharmacology, 2019)
Scopoletin, a phenolic coumarin derived from many medical or edible plants, is involved in various pharmacological functions. In the present study, we showed that Scopoletin effectively ameliorated experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), through novel regulatory mechanisms involving inhibition of NF-κB activity in dendritic cells (DCs). Scopoletin treatment significantly improved the severity of the disease and prominently decreased inflammation and demyelination of central nervous system (CNS) in EAE mice. Disease alleviation correlated with the down-regulation of MHC class II, CD80 and CD86, expressed on DCs of CNS or spleens, and the infiltration and polarization of encephalitogenic Th1/Th17 cells. Consistent with the in vivo data, Scopoletin-treated, bone marrow-derived dendritic cells (BM-DCs) exhibited reduced expression of MHC class II and co-stimulatory molecules (e.g., CD80 and CD86) and reduced NF-κB phosphorylation. These findings, for the first time, demonstrated the ability of Scopoletin to impair DC activation, down-regulating pathogenic Th1/Th17 inflammatory cell responses, eventually, reducing EAE severity. Our study demonstrates new evidence that natural products derived from medical or edible plants, such as Scopoletin, will be valuable in developing a novel therapeutic agent for MS in the future.